Gamification, strategyshared betweenuniversity, companyand millennials - A. de los Ríos; Y. Muñoz; P. Castro; J. L. Arroyo (Universitat Politècnica de València, 2019)
In the European Space of Higher Education, the cultural features of the millennials, the development of technology and the shift in the understanding of the students' learning process, have played a vital role  in the development and evolution of gamification-based teaching practices. Gamification is related to the development of skills, motivation and commitment of students. The aim of this paper is to provide evidence of the benefits of gamification in the training itinerary of Business Administration students. To this end, two different experiences have been selected, based on the skills students train and the added value that these skills may provide. In the first case, this paper presents empirical evidence of the improvement on the final grade of students who have participated in the gamification experience. The benefits of the second experience are diverse and  reach students, universities and companies. The success of both experiences is linked to their adaptation to the cultural traits of the millennials, whose learning process is conditioned by technology and by other features identified in literature. The second experience responds to the necessary  collaboration between university and business, as well as the generation of networks.